Rheology of Biological Soft Matter Fundamentals and Applications - Kaneda, Isamu; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
In this book, a wide range subjects in biorheology are dealt with, from fundamentals to applications. The inclusion of quite substantial chapters concerned with application aspects such as the latest studies on foods, cosmetics, personal care products, and biological tissues, related regenerative medicine, is one of the features of the book. For the fundamental aspects, studies on the physicochemical characteristics of biopolymer, the key substance of soft matter, are listed. By contrast, in the application aspect, although the main topic is the rheology of foods, focusing on the "texture" of mastication or swallowing, novel studies on cosmetics and personal care products concerning feeling during the lubrication by those products are also considered. This book will engage both a professional and an academic audience interested in soft matter, especially as related to food, cosmetics, and personal care products. In particular, this work willhave a special appeal to scientists and engineers in the food and cosmetics industries and to graduate students preparing for those fields.
Bridging the gap between single molecule unbinding properties and macromolecular rheology -- Zero-Shear Viscosities of Polysaccharide Solutions -- Gel-Solvent Friction -- Swallowing and the rheological properties of soft drink and agar gel -- Moisture Distributions and Properties of Pasta Prepared or Cooked under Different Conditions -- Moisture Distributions and Properties of Pasta Prepared or Cooked under Different Conditions -- Rheological Studies on Gelation Kinetics of Powdered Soybean in the presence of Glucono-δ-Lactone -- Linkage between food rheology and human physiology during oral processing -- Gelation characteristics of heat-induced gels mixed meat with fish proteins -- Rheology modifiers for the management of dysphagia -- The effect of Preparation Conditions on the rheological properties of Gomatofu (Sesame tofu) -- Rheology control agents for cosmetics -- Rheological Properties of Personal Lubricants -- Development of PVA Hydrogels with Superior Lubricity for Artificial Cartilage -- Physical Properties of Pig Vitreous Body. .
Keywords: Food science; Soft condensed matter; Biomaterials; Chemistry, Technical; Polymers; Food Science; Soft and Granular Matter; Biomaterials; Industrial Chemistry; Polymers